2019
DOI: 10.3390/land8110167
|View full text |Cite
|
Sign up to set email alerts
|

Tree Wind Breaks in Central Asia and Their Effects on Agricultural Water Consumption

Abstract: Across Central Asia, agriculture largely depends on irrigation due to arid and semi-arid climatic conditions. Water is abstracted from rivers, which are largely fed by glacier melt. In the course of climate change, glaciers melt down so that a reduced glacier volume and reduced water runoffs are expected to be available for irrigation. Tree wind breaks are one option to reduce water consumption in irrigated agriculture and build resilience against climate change. This paper therefore assesses the water consump… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…It regulates the ecosystem by lessening the impact of wind and water erosion. The dense cactus vegetation can substantially reduce soil evaporation, and when intercropping systems are used, cacti can reduce the amount of water necessary for healthy plant growth [ 27 , 28 ]. It is reported that in Tunisia and Algeria, Prickly-pears are planted in contour-like patterns to maximize the efficiency of water runoff harvesting and to control soil erosion on hillslopes [ 29 ].…”
Section: Combating Desertification and Improving Soil Health With ...mentioning
confidence: 99%
“…It regulates the ecosystem by lessening the impact of wind and water erosion. The dense cactus vegetation can substantially reduce soil evaporation, and when intercropping systems are used, cacti can reduce the amount of water necessary for healthy plant growth [ 27 , 28 ]. It is reported that in Tunisia and Algeria, Prickly-pears are planted in contour-like patterns to maximize the efficiency of water runoff harvesting and to control soil erosion on hillslopes [ 29 ].…”
Section: Combating Desertification and Improving Soil Health With ...mentioning
confidence: 99%
“…In the case of limited water resources in arid oases, oasis expansion and oasis agriculture development, coupled with the application of water-saving facility agriculture and considering the impact of climate change, not only altered the water consumption trend in shelterbelts but also restricted the water resource supply [11,17,18] . Solar radiation, rainfall, air temperature and humidity affect the transpiration rate and water consumption of shelterbelts, and normal shelterbelt development cannot occur without a timely supply of ecological water [5,19,20] . Climate change and frequent agricultural activities have caused an imbalance in the water resource distribution in oases, leading to the crowding out of ecological water resources in shelterbelts [21][22][23] .…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, poplars were planted along field borders and irrigation ditches to gain wood as construction material, without occupying much space of adjacent crop fields. During Soviet Union times, those poplar rows along field borders were propagated as tree wind breaks to reduce wind speed, improve the micro climate, and help to increase crop yields [2][3][4][5]. Thereby, the effects on the microclimate and crop yields were the main target rather than the wood resources potentially provided from such tree wind breaks [6][7][8].…”
Section: Introductionmentioning
confidence: 99%